2002
DOI: 10.1354/vp.39-4-452
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and Biologic Behavior of Pleomorphic Cutaneous Mast Cell Tumors in Fifteen Cats

Abstract: Most feline cutaneous mast cell tumors (CMCT) are behaviorally benign; however, there is a subset of these tumors with, marked pleomorphism (previously termed poorly differentiated) that have been reported to be more aggressive. In this study, pleomorphic CMCT from 15 cats were identified from surgical biopsy submissions, and follow-up clinical data were obtained for 14 of these cats. Pleomorphic CMCT were discrete dermal nodules composed of sheets of pleomorphic round cells. Tumors from all 15 cats contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 5 publications
2
63
2
5
Order By: Relevance
“…The 20% of MCTs with malignant behavior in this series was similar to that observed in previous studies. 3,4,15,18,19,26,34,36 In contrast to studies in which male cats had higher prevalence of MCTs, 3,22 the male:female ratio in this study favored females, but sex was not correlated with outcome. The reported tendency of young Siamese cats to develop benign atypical cutaneous MCTs 36 was not evident; the only Siamese cat in this study was 15 years old and died with a disseminated mastocytic pleomorphic MCT.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…The 20% of MCTs with malignant behavior in this series was similar to that observed in previous studies. 3,4,15,18,19,26,34,36 In contrast to studies in which male cats had higher prevalence of MCTs, 3,22 the male:female ratio in this study favored females, but sex was not correlated with outcome. The reported tendency of young Siamese cats to develop benign atypical cutaneous MCTs 36 was not evident; the only Siamese cat in this study was 15 years old and died with a disseminated mastocytic pleomorphic MCT.…”
Section: Discussioncontrasting
confidence: 67%
“…Some authors reported high mitotic activity in pleomorphic MCTs, 10,11 whereas the mitotic index (MI) was variable but usually low in another study. 15 Pleomorphic MCTs are often more heavily infiltrated by eosinophils. [10][11][12] The atypical feline cutaneous MCT is rare and reported mainly in juvenile to middle-aged Siamese cats, in which it may spontaneously regress.…”
mentioning
confidence: 99%
See 3 more Smart Citations